Efficient Hybrid Grouping Spectrum Assignment to Suppress Spectrum Fragments in Flexible Grid Optical Networks - Qiu, Yang; Xu, Jing (Journal of lightwave technology, 2017)
Flexible grid optical networks (FONs) can accommodate diverse kinds of service connections with higher networking flexibility and spectrum-utilization efficiency by employing a finer resource allocation granularity (known as frequency slot) and a more sophisticated path-routing and resource-allocation algorithm (known as routing and spectrum assignment algorithm), when compared to the traditional wavelength division multiplexing optical networks. However, the continuity and the contiguity constraints in spectrum allocation may possibly introduce spectrum fragments, which cannot be utilized by the subsequent service connections and thus reduce the amount of available resources as well as the networking flexibility in FONs. Therefore, many algorithms have been proposed to decrease the amount of spectrum fragments by re-optimizing the fragmented resources. These algorithms are known as spectrum defragmentation algorithms, which always induce traffic disruption or require extra components. In order to avoid traffic disruption and the requirement of extra components, some grouping RSA algorithms have been proposed to suppress spectrum fragments from their generation by pre-dividing the spectrum resources into several either fixed or variable groups. However, since the spectrum resources in one group can only be assigned to the service connections of one specific kind, the flexibility of these grouping algorithms is always limited by the kinds of service connections. In this paper, we introduce hybrid grouping mechanism into spectrum assignment and propose a hybrid-group-based RSA algorithm, most-used-first hybrid grouping (MUFHG) RSA algorithm, to suppress the spectrum fragments generated in FONs. By employing hybrid grouping mechanism, the proposed MUFHG algorithm sorts the spectrum resources into several flexible groups with specified allocation starting FSs. And each spectrum group can accommodate several kinds of service connections if the bandwidth requirements of these service connections have multiple relations, which guarantees that the remained or the released spectrum resources in each group can always be re-used. Therefore, spectrum fragments are only generated in the spectrum bands between two adjacent flexible groups. In this way, the proposed hybrid-group-based algorithm can significantly suppress spectrum fragments from their generation. Besides, the proposed MUFHG algorithm helps improve the blocking performance of the network by employing the most-used-first strategy to maximize the number of less frequently used spectrum resources for subsequent service connections. The simulation results indicate that the proposed MUFHG algorithm gains notable reductions in both spectrum fragments and bandwidth blocking probability with neither traffic disruption nor extra components.